Metal organic framework material and preparation method thereof, and metal organic framework composite wood and preparation method thereof

By combining MOFs with 1,3,5-benzenetriacetic acid and long-chain alkyl modifier and synthesized in situ in wood, the problems of MOFs molding and moisture sensitivity are solved, and the efficient adsorption of VOC of metal-organic frame composite wood is achieved.

CN119820674APending Publication Date: 2025-04-15GUIZHOU ACAD OF FORESTRY SCI
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202510023451.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-07
Publication Date
2025-04-15

AI Technical Summary

Technical Problem

Metal organic frame materials (MOFs) are prone to agglomeration, difficult to form, and are easily affected by moisture, limiting their practical application in indoor pollutant adsorption applications.

Method used

By combining MOFs with 1,3,5-benzenetriacetic acid and long-chain alkyl modifiers, a metal organic frame material is designed and synthesized in situ in wood to form a metal organic frame composite wood. The method includes reacting with copper ion solution, 1,3,5-benzenetriacetic acid, organic solvent and long-chain alkyl modifier, and activation under high temperature vacuum conditions to improve the hydrophobic properties and adsorption capacity of the material.

Benefits of technology

The stable molding of MOFs is achieved and its hydrophobic properties is improved, and the molding and moisture sensitivity problems of MOFs in practical applications are overcome. The material has shown good results in adsorption of volatile organic compounds (VOCs).

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119820674A_ABST
    Figure CN119820674A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of wood functional modification, and discloses a metal organic framework material and a preparation method thereof, and metal organic framework composite wood and a preparation method thereof. The metal organic framework material is prepared from the following raw materials in parts by mass: 50 to 100 parts of copper ion solution, 10 parts of 1, 3, 5-benzenetricarboxylic acid, 80 to 100 parts of organic solvent, 80 to 100 parts of ethanol and 10 to 15 parts of long-chain alkyl modifier. In addition, the treated metal organic framework material is obtained by combining the metal organic framework material with a pressure impregnation process of specific steps. The MOFs material provided by the invention is simple in component and relatively low in production cost, the MOFs modified by long-chain alkyl are high in hydrophobicity and not prone to agglomeration, the process for treating materials such as wood is simple, and the effect is excellent; the obtained wood has the performance of adsorbing volatile organic compounds (VOC).
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of wood functional modification, and in particular relates to a metal organic framework material and a preparation method thereof, a metal organic framework composite wood and a preparation method thereof. Background Art

[0002] There are many sources of indoor pollutants, such as indoor fuel combustion and cleaning products. Volatile organic compounds (VOCs) are an important component of indoor pollutants, mainly composed of C6-C16 aromatic hydrocarbons, aliphatic hydrocarbons, alcohols, aldehydes, ketones and esters. Short-term exposure to high concentrations of VOCs indoors can cause health effects, such as headaches, nausea, respiratory infections, allergies and asthma, and long-term exposure can cause cancer in humans. Therefore, the concentration of indoor VOCs is regulated by various national / international agencies, and minimizing anthropogenic VOC emissions is a top priority. At present, many technologies including adsorption, catalytic oxidation, absorption, condensation and biodegradation have been developed for VOC purification. Among them, adsorption is considered to be one of the most promising and widely used methods in terms of both technical effectiveness and economic benefits. The development of low-cost and efficient adsorbents is crucial to the adsorption method.

[0003] Metal-organic frameworks (MOFs) are crystalline materials composed of metal ions or clusters and organic ligands. MOFs materials mainly include reticulated metal-organic frameworks (IRMOFs), Lavoisier Institute materials (MILs), pocket channel frameworks (PCNs) and imidazolate zeolite frameworks (ZIFs). They have the characteristics of high specific surface area, diverse pore structures and rich active sites, and have great application potential in gas storage, catalysis, antibacterial and other fields. In addition, MOFs are ideal for gas adsorption and sensing due to their wide tunability and complexation with gases, which is attributed to the π-π interaction with gases. However, as a powdery crystalline material, MOFs are easy to agglomerate, have poor processability, are difficult to shape and are easily affected by moisture, which greatly limits their practical application.

[0004] Therefore, there is currently a lack of a metal organic framework material and a processing method thereof to overcome its molding shortcomings and realize practical application in indoor pollutant emissions. Summary of the invention

[0005] The technical problem to be solved by the present invention is that MOFs are easy to agglomerate, difficult to shape and easily affected by moisture, and overcome the deficiencies and defects mentioned in the above background technology, and provide a metal organic framework material, a metal organic framework composite wood and a preparation method thereof.

[0006] In order to solve the above technical problems, the technical solution proposed by the present invention is: A metal organic framework material comprising the following raw materials in parts by weight: 50-100 parts of copper ion solution, 10 parts of 1,3,5-benzenetricarboxylic acid, 80-100 parts of organic solvent, 80-100 parts of ethanol, and 10-15 parts of long-chain alkyl modifier.

[0007] Composite MOFs with other porous substrates is an effective strategy to overcome their inherent defects. This application designs a metal organic framework material with simple components and relatively low production cost. 1,3,5-Benzenetricarboxylic acid has a self-organized 2D molecular network structure, excellent comprehensive performance and relatively low price. The long-chain alkyl modifier modifies the surface of the synthesized MOF to make its surface rough and thus improve its hydrophobic properties.

[0008] Preferably, the copper ion solution comprises copper nitrate, and the mass concentration of the copper ion solution is 10-15%; the organic solvent comprises N,N-dimethylformamide; and the long-chain alkyl modifier comprises octadecylamine. 18 H 39 N), when the MOF surface is effectively covered by the alkyl long chain, the surface energy of MOF decreases and the surface structure becomes rough (e.g. Figure 3 As shown in d and e in the figure, this change can improve the hydrophobicity of the material. The specific mechanism of the modification process is as follows Fig.15 As shown, the N atoms on the octadecylamine coordinate with the metal ions in the MOF, so that the octadecylamine is fixed on the MOF surface.

[0009] Under the same technical concept, the present application also provides a method for preparing a metal organic framework material, which specifically comprises the following steps: (1) The copper ion solution, 1,3,5-benzenetricarboxylic acid, organic solvent and ethanol are stirred evenly, sealed, and kept at 85-90°C for 18-22 hours; washed, heated at 120-150°C under vacuum conditions for 3-5 hours, filtered, and the obtained precipitate is a metal organic framework material precursor; (2) Mixing the metal organic framework material precursor described in step (1) with a long-chain alkyl modifier in an ethanol solution, stirring at 120-150° C. for 22-26 h under an inert gas atmosphere, removing the solution, washing, and heating at 120-150° C. under vacuum conditions for 3-5 h to obtain a metal organic framework material.

[0010] More preferably, the washing is carried out using ethanol.

[0011] Under the same technical concept, the present application also provides a metal organic framework composite wood, wherein the metal organic framework composite wood uses wood as a carrier and carries the metal organic framework material described above.

[0012] Wood is a widely used indoor building and decoration material. It is an environmentally friendly natural porous material with an ordered pore structure, excellent mechanical properties and abundant active groups, making it an ideal carrier for MOFs. Wood is mainly composed of tubular cells (such as vessels, tracheids and fibers) arranged in an orderly manner along the growth direction. These highly oriented cell channels and abundant pore structures can provide space for the in-situ growth of MOFs. The wood cell wall is a natural polymer composite material with cellulose as the skeleton material and lignin / hemicellulose as the binding (shell) material tightly interwoven. It is rich in active groups such as hydroxyl and carboxyl groups, which can provide nucleation sites for the in-situ growth of MOFs.

[0013] Preferably, the wood comprises poplar.

[0014] More preferably, the size of the wood is 10 mm×20 mm×20 mm (longitudinal×tangential×radial), and the density is 0.63 g / m 3 This size is convenient for processing and use in VOC adsorption experiments.

[0015] Under the same technical concept, the present application also provides a method for preparing the metal organic framework composite wood, which adopts a solvent thermal synthesis method to synthesize the metal organic framework material in situ in the wood. When the wood is impregnated with a metal ion solution, the hydroxyl carboxyl groups on the cellulose molecular chain can coordinate with the metal ions, so that the metal ions are fixed in the wood, providing nucleation sites for the growth of MOF; when the ligand material is added, the MOF will be generated in situ on the wood. This reaction mode can cover various tissues inside the wood (such as vessels, fibers, wood rays, etc.), making the distribution of MOF in the wood more uniform.

[0016] Preferably, the method specifically comprises the following steps: (1) Immersing the wood in a copper ion solution under pressure, taking out the wood, adding 1,3,5-benzenetricarboxylic acid, an organic solvent and ethanol, stirring evenly, sealing, and maintaining at 85-90°C for 18-22 hours; washing, and heating at 120-150°C under vacuum conditions for 3-5 hours to obtain an activated metal organic framework modified wood; (2) The metal organic framework modified wood and the long chain alkyl modifier are placed in an ethanol solution, stirred at 120-150° C. for 22-26 hours under an inert gas atmosphere, the solution is removed, washed, and heated at 120-150° C. under vacuum conditions for 3-5 hours to obtain a metal organic framework composite wood.

[0017] More preferably, the washing is carried out using ethanol.

[0018] The modified MOF is synthesized in situ in the wood. In the process of synthesizing the metal organic framework material, the hydrophobic MOF covers the wood surface, which can also improve the hydrophobicity of the wood, thereby avoiding the influence of moisture on the metal organic framework composite wood. The moisture and other residual gases in the MOF material are volatilized under high temperature and vacuum conditions, making the synthesized metal organic framework composite wood suitable for the adsorption of volatile gases such as toluene.

[0019] Preferably, the immersion pressure is 1 to 1.2 standard atmospheres; and the immersion time is 10 to 14 hours.

[0020] Compared with the prior art, the present invention has the following beneficial effects: (1) The metal organic framework material provided in this application has simple components and relatively low production costs. The MOFs modified with long-chain alkyl groups are highly hydrophobic and not easy to agglomerate. In addition, the treatment process for materials such as wood is simple and has excellent effects. (2) The metal-organic framework composite wood provided in this application uses wood as a carrier. The cellulose, lignin and hemicellulose in the wood are rich in active groups such as hydroxyl and carboxyl groups, which can provide nucleation sites for the in situ growth of MOFs, further enhancing the binding effect between MOFs and wood. The prepared metal-organic framework composite wood has the function of adsorbing VOCs. BRIEF DESCRIPTION OF THE DRAWINGS

[0021] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.

[0022] Figure 1 Schematic diagram of formaldehyde dynamic adsorption experimental device of Example and Comparative Example; Figure 2 : SEM images of wood treated with MOFs obtained in the examples, wherein a is an SEM image of untreated wood, b is a distribution image of MOF materials in wood treated with MOF199, and c is a distribution image of MOF materials in wood treated with HMOF199; Figure 3 d is an SEM image of the MOFs obtained in the example; wherein, d is an enlarged image of the metal organic framework (labeled as MOF199), and e is a metal organic framework modified with octadecylamine (labeled as HMOF199); Figure 4 The dynamic adsorption curve of toluene by the wood treated with Examples 1-2 and Comparative Examples 1-3 under dry conditions; Figure 5It is a bar graph of the adsorption capacity of toluene by the wood treated with Examples 1-2 and Comparative Examples 1-3 under dry conditions; Figure 6-9 The dynamic adsorption curves of toluene by the wood treated with Examples 1-2 and Comparative Examples 2-3 under different humidity conditions; Figure 10-13 This is a bar graph of the toluene adsorption capacity of the wood treated with Examples 1-2 and Comparative Examples 2-3 under different humidity conditions; Fig.14 This is the toluene adsorption curve of the metal organic framework modified wood (MIL(Fe)) of Comparative Example 4; Fig.15 This is a diagram showing the mechanism of the metal organic framework material of the present invention. DETAILED DESCRIPTION

[0023] In order to facilitate the understanding of the present invention, the present invention will be described more comprehensively and meticulously below in conjunction with the accompanying drawings and preferred embodiments of the present invention, but the protection scope of the present invention is not limited to the following specific embodiments.

[0024] Unless otherwise defined, all professional terms used below have the same meanings as those generally understood by those skilled in the art. The professional terms used herein are only for the purpose of describing specific embodiments and are not intended to limit the scope of protection of the present invention.

[0025] Unless otherwise specified, various raw materials, reagents, instruments and equipment used in the present invention can be purchased from the market or prepared by existing methods.

[0026] Example 1 This embodiment provides a metal organic framework material, the raw materials include 10 g Cu (NO3) 2, 10 g 1,3,5-benzenetricarboxylic acid, 83.3 mL DMF and 83.3 ml ethanol, 250 mL 0.1 M octadecylamine; This embodiment provides a method for preparing a metal organic framework material, which specifically includes: (1) A copper nitrate solution of 10 g Cu(NO3)2·3H2O and 83.3 mL deionized water was mixed with 1,3,5-benzenetricarboxylic acid (H3BTC, 10 g), DMF (83.3 mL) and ethanol (83.3 ml), and treated under ultrasonic stirring for 30 min. The mixture was sealed and kept at 85 °C for 20 h, washed with ethanol, and heated at 150 °C under vacuum for 5 h to reach an activated state. The mixture was filtered to obtain a metal organic framework material precursor (labeled as MOF199). (2) The metal organic framework material precursor was stirred with 250 mL of 0.1 M octadecylamine ethanol solution under N2 protection for 24 hours at 120 °C, and then the solution was removed, washed with ethanol, and vacuum activated at 150 °C for 5 hours to obtain a metal organic framework material (labeled as HMOF199).

[0027] Embodiment 2: The metal organic framework composite wood provided in this embodiment uses poplar wood with a size of 10 mm×20 mm×20 mm (longitudinal×tangential×radial) to load the metal organic framework material.

[0028] This embodiment also provides a method for preparing a metal organic framework composite wood, which specifically comprises the following steps: (1) The size is 20*20*200 mm and the density is 0.63g / m 3 The poplar wood was immersed in a copper nitrate solution containing 10 g Cu(NO3)2·3H2O and 83.3 mL deionized water at 1.1 atmospheres for 10 hours. Subsequently, the pressure was released, the wood was taken out, 1,3,5-benzenetricarboxylic acid (H3BTC, 10 g), DMF (83.3 mL) and ethanol (83.3 ml) were added to a container, the wood was put in, and the container was sealed after being treated under ultrasonic stirring for 30 min and kept at 85 °C for 20 h to prepare a metal organic framework modified wood (labeled as MOF199-W); the obtained metal organic framework modified wood was transferred to ethanol and washed three times to remove unreacted chemicals, and then heated at 150 °C under vacuum for 5 h to reach an activated state, filtered, and the obtained precipitate was a metal organic framework material precursor; (2) The metal-organic framework material modified wood was stirred in 250 mL of 0.1 M octadecylamine ethanol solution under N2 protection at 120 °C for 24 hours, then the solution was removed and the remaining sample was washed three times with ethanol to ensure the removal of excess octadecylamine; the washed sample was vacuum activated at 150 °C for 5 hours to obtain a metal-organic framework composite wood (labeled as HMOF199-W).

[0029] Comparative Example 1: Comparative Example 1 is an untreated poplar wood with dimensions of 10 mm×20 mm×20 mm (longitudinal×tangential×radial) and a density of 0.63 g / m 3 (marked as W).

[0030] Comparative Example 2: Comparative Example 2 is the metal organic framework material precursor in Example 1 (labeled as MOF199).

[0031] Comparative Example 3: Comparative Example 3 is the metal organic framework modified wood in Example 2 (labeled as MOF199-W).

[0032] The surface morphology of the metal organic framework materials and metal organic framework composite wood obtained in the examples and comparative examples was detected by scanning electron microscope. Figure 2 , 3 shown.

[0033] Among them, (a) is the untreated poplar wood (W) of Comparative Example 1, (b) is the metal organic framework modified wood (marked as MOF199-W) in Example 2, (c) is the metal organic framework composite wood (marked as HMOF199-W) of Example 2, (d) is an enlarged view of the metal organic framework (marked as MOF199), and (e) is the metal organic framework modified by octadecylamine (marked as HMOF199). Figure 2 As shown in (a), the untreated wood fibers, vessels, and other tissues show a smooth and uniform surface. Figure 2 In (b) and (c), the surface of the wood tissue is covered with a crystal layer, and the distribution of the crystals can be identified as MOF199 or HMOF199 crystals.

[0034] The VOC adsorption performance of the metal organic framework material modified wood and the metal organic framework material obtained in the examples and comparative examples was tested, and the test process and results are as follows: Detection method: Toluene is used as the adsorbed material, and a dynamic adsorption test of toluene by the material is carried out on a self-designed adsorption device (the schematic diagram of the formaldehyde dynamic adsorption experimental device is shown in Figure 1 ). Before the test, the sample was activated under vacuum at 150 °C for 5 hours. Toluene gas was mixed by three gas pipelines, among which nitrogen was introduced into the toluene solution through V-2 to form toluene gas, and another V-3 was used as a balance gas to control the initial concentration of toluene, and the humidity was adjusted by V-1 through distilled water. The adsorption experiment was carried out at 25 °C, and the initial and final concentrations of toluene were monitored by a VOCs detector (HYS1002). The adsorption conditions were as follows: the initial concentration of toluene was 1000 mg / m 3 , the flow rate is 400 mL / min. The adsorption capacity (mg / g) was calculated according to equation (1), where Q is the gas flow rate of the gas flow (L / min), t is the adsorption time (min), and C0 is the initial toluene concentration (mg / m 3 ), Ct is the final concentration of toluene, and m is the mass of the adsorbent used (g). When Ct / C0≥0.95, the adsorption reaches saturation.

[0035] Adsorption capacity = (1) The dynamic adsorption curve and adsorption capacity of toluene under the dry conditions of Examples 1-2 and Comparative Examples 2-3 are as follows: Figure 4 , 5 As shown. Figure 4 In the experiment, MOF199 showed good adsorption effect, with an adsorption capacity of 369.9 mg / g for toluene. After the introduction of octadecylamine, the adsorption capacity of MOF199 was still retained. Compared with the untreated wood (W), the increase phase of toluene concentration in MOF199-W was significantly delayed, and the increase rate was reduced, indicating that MOF199-W had a good adsorption effect. At the same time, the adsorption capacity of HMOF199 and HMOF199-W, which have higher hydrophobicity, did not decrease significantly compared with MOF199 and MOF199.

[0036] Toluene adsorption curves and adsorption capacities at four different relative humidity levels (10, 20, 40, and 80%) are shown in Figure 2. Figure 6-13 shown. Figure 6-9 The following is a dynamic adsorption curve of toluene by treated wood under different humidity conditions; wherein: Figure 6 For MOF199 in Comparative Example 2, Figure 7 For MOF199-W in Comparative Example 3, Figure 8 is HMOF199 in Example 1, Fig. 9 HMOF199-W in Example 2; Figure 10-13 The bar graph is a graph showing the toluene adsorption capacity of the treated wood under different humidity conditions. Fig.10 For MOF199 in Comparative Example 2, Fig.11 For MOF199-W in Comparative Example 3, Fig.12 is HMOF199 in Example 1, Fig.13 It is HMOF199-W in Example 2.

[0037] Humidity has an adverse effect on the adsorption properties of MOF199 and MOF199W. As the relative humidity increases from 0 to 80%, the adsorption penetration time of toluene on MOF199 and MOF199W decreases rapidly, and the adsorption capacity decreases from 270.2 and 190.3 to 113.0 and 147.9 mg / g. The adsorption behavior of HMOF199 and HMOF199W is less affected by moisture. Under high humidity (RH=80%) conditions, as the relative humidity increases from 0% to 80%, the adsorption penetration time of HMOF199 and HMOF199W for toluene is moderately shortened, and the adsorption capacity is maintained.

[0038] Comparative Example 4: This comparative example provides a metal organic framework material, the raw materials include 12.12 g Fe (NO3) 39H2O, 6 mmol 1,3,5-benzenetricarboxylic acid, 300 mL deionized water; The metal organic framework composite wood provided in this comparative example uses wood with a size of 10 mm×20 mm×20 mm (longitudinal×chordal×radial) to load the metal organic framework material.

[0039] This comparative example also provides a method for preparing a metal organic framework composite wood, which specifically comprises the following steps: (1) A piece of wood with a size of 20*20*200 mm was immersed in a ferric nitrate solution containing 12.12 g Fe(NO3)39H2O and 300 mL deionized water at 1.1 atmospheres for 10 h. Subsequently, the pressure was released, 1,3,5-benzenetricarboxylic acid (H3BTC, 3 mmol) was added to the container, and after continuous stirring for 15-30 min, it was transferred to a 500 ml reactor and kept at 150 °C for 12 h to prepare a metal organic framework modified wood (labeled as MIL(Fe)-W); the obtained was transferred to ethanol and washed three times to remove unreacted chemicals, and then heated at 150 °C under vacuum conditions for 5 h to achieve an activated state.

[0040] Detection method: Toluene was used as the adsorbed material and the test was carried out according to the adsorption method in the above-mentioned examples and comparative examples.

[0041] From the results of the toluene dynamic adsorption test, it can be seen that ( Fig.14 ), the concentration of toluene in the untreated wood increased rapidly in a very short time. Compared with the untreated wood, the rising stage of toluene concentration in MIL(Fe)-W was significantly delayed and the rising rate was reduced, indicating that the metal organic framework modified wood has a good adsorption effect, and also proved the feasibility of wood-MOFs for VOC adsorption; but the wood in the comparative example failed to achieve the technical effect of the present application.

Claims

1. A metal organic framework material, characterized in that: Contains the following raw materials by mass: 50-100 parts of copper ion solution, 10 parts of 1,3,5-benzenetricarboxylic acid, 80-100 parts of organic solvent, 80-100 parts of ethanol, and 10-15 parts of long-chain alkyl modifier.

2. The metal organic framework material according to claim 1, characterized in that: The copper ion solution comprises copper nitrate, and the mass concentration of the copper ion solution is 10-15%; the organic solvent comprises N,N-dimethylformamide; and the long-chain alkyl modifier comprises octadecylamine.

3. A method for preparing a metal organic framework material, characterized in that: The specific steps include: (1) The copper ion solution, 1,3,5-benzenetricarboxylic acid, organic solvent and ethanol are stirred evenly, sealed, and kept at 85-90°C for 18-22 hours; washed, heated at 120-150°C under vacuum conditions for 3-5 hours, filtered, and the obtained precipitate is a metal organic framework material precursor; (2) Mixing the metal organic framework material precursor described in step (1) with a long-chain alkyl modifier in an ethanol solution, stirring at 120-150° C. for 22-26 h under an inert gas atmosphere, removing the solution, washing, and heating at 120-150° C. under vacuum conditions for 3-5 h to obtain a metal organic framework material.

4. A metal organic framework composite wood, characterized in that: The metal organic framework composite wood uses wood as a carrier and carries the metal organic framework material according to any one of claims 1 to 2.

5. The metal organic framework composite wood according to claim 4, characterized in that: The wood includes poplar.

6. A method for preparing a metal organic framework composite wood according to any one of claims 1 to 2, characterized in that: The preparation method adopts a solvent thermal synthesis method to synthesize the metal organic framework material in situ in wood.

7. The preparation method according to claim 6, characterized in that: The specific steps include: (1) Immersing the wood in a copper ion solution under pressure, taking out the wood, adding 1,3,5-benzenetricarboxylic acid, an organic solvent and ethanol, stirring evenly, sealing, and maintaining at 85-90°C for 18-22 hours; washing, and heating at 120-150°C under vacuum conditions for 3-5 hours to obtain an activated metal organic framework modified wood; (2) The metal organic framework modified wood and the long chain alkyl modifier are placed in an ethanol solution, stirred at 120-150° C. for 22-26 hours under an inert gas atmosphere, the solution is removed, washed, and heated at 120-150° C. under vacuum conditions for 3-5 hours to obtain a metal organic framework composite wood.

8. The preparation method according to claim 6, characterized in that: The pressurized pressure during immersion in the copper ion solution is 1 to 1.2 standard atmospheres; the immersion time is 10 to 14 hours.

Citation Information

Cited By

  • Soybean meal extracting solution mediated high-dispersion copper-based MOF composite material as well as preparation method and application thereof

    CN122427395A